2021
DOI: 10.1016/j.linged.2021.100905
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how language exposure shapes oral narrative skills in French-English emergent bilingual first graders

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…However, the finding of this study revealed that non-interactive Extramural English was essential. Although not every participant was exposed to interactive language, all of them reported regularly watching, reading, and using English language settings on their devices, which was supported by their positive parental attitude towards language learning and their educational or economic background (Altinkamis & Simon, 2020;Cantone, 2022;Cohen et al, 2021;De Houwer, 2017). The participants in the present study made fewer errors in clarity, punctual and grammar (1%-29%) compared to a previous study by Mustafa et al (2017).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, the finding of this study revealed that non-interactive Extramural English was essential. Although not every participant was exposed to interactive language, all of them reported regularly watching, reading, and using English language settings on their devices, which was supported by their positive parental attitude towards language learning and their educational or economic background (Altinkamis & Simon, 2020;Cantone, 2022;Cohen et al, 2021;De Houwer, 2017). The participants in the present study made fewer errors in clarity, punctual and grammar (1%-29%) compared to a previous study by Mustafa et al (2017).…”
Section: Discussionsupporting
confidence: 62%
“…It has been found that mothers with greater levels of education and parents from higher socioeconomic backgrounds are more likely to encourage their children to acquire a second language (Brown, 2021). Parents might assume the role of agents when they teach their children to speak English at home (Cohen et al, 2021) or provide learning facilities to their children, for example, by reading books or accessing videos that support language acquisition (Azzolini et al, 2020).…”
Section: Literature Review Extramural Englishmentioning
confidence: 99%
See 1 more Smart Citation
“…Practice encompasses both the strategies employed and language use. It is indicated to influence bilingual language outcomes (Cohen et al 2021). However, parents may be oblivious to strategies that they employ (De Houwer and Nakamura 2022).…”
Section: Family Language Policymentioning
confidence: 99%
“…On ve continents, 200 million people speak French. French is a major language used for international communication and is one of the most studied foreign languages after English, ranking ninth among the most spoken languages in the world [5,6]. Mastering French allows one to communicate with French speakers from all continents while expressing another perspective on the world, and to bene t from wellinformed international media in French (e.g., TV5, France 24, and Radio France International) [7,8].…”
Section: Introductionmentioning
confidence: 99%